Social Ties, Social Capital, and Recruiting Managers in Transnational Ventures. Issue 2 (3rd April 2017) - Pruthi, Sarika; Wright, Mike
ABSTRACT: Social capital provides access to resources; however, how migrant entrepreneurs use social capital in the recruitment of managers for their transnational ventures is less understood. The authors conducted eight in-depth interviews with transnational entrepreneurs of Indian origin in the United Kingdom and nine confirmatory interviews with managers of their transnational ventures. Findings show that transnational entrepreneurs substitute or complement international and local social capital in the recruitment of managers contingent on whether they (a) live in the United Kingdom or India and (b) use social ties in the United Kingdom or India to recruit managers. Implications for research, policy and management are discussed.